Economically Justified Levels of Road Works Expenditures on Unpaved Roads - Archondo-Callao, Rodrigo (World Bank, Washington, DC, 2012)
Unpaved roads require periodic road works to maintain a certain road condition over time, comprising typically of routine maintenance, grading, spot regravelling, and regravelling activities, which require planning and economic justification. A main concern in developing counties is defining a proper level of investments and quality of maintenance on unpaved roads. This technical note, targeted to road sector professionals, presents a methodology for an analytical study done to access economically justified levels of road works expenditures on unpaved roads with different traffic levels. The results presented in this technical note should be considered no more than a first approximation of country specific results. To obtain country specific results, the methodology should be replicated and adapted with refined country data.